The Origin of Species - Charles Darwin (Simon & schuster paperbacks, 2009)
This classic work of scientific literature, presenting the theory of evolution by means of natural selection, is still both relevant and controversial in the twenty-first century. THIS ENRICHED CLASSIC EDITION INCLUDES: A concise introduction that gives the reader important background information A chronology of the author\'s life and work A timeline of significant events that provides the book\'s historical context An outline of key themes to guide the reader\'s own interpretations Detailed explanatory notes Critical analysis, including contemporary and modern perspectives on the work Discussion questions to promote lively classroom and book group interaction